Protocol for assessment of CRISPR base editors and their components in Escherichia coli - Rahul Mahadev Shelake; Jae-Yean Kim (STAR Protocols, 2025)
Summary: Base editing (BE) is a CRISPR technique that allows precise nucleobase conversions. However, high expression of BE components is often toxic in Escherichia coli. Here, we present a protocol for analyzing BE at single or multiple target sites using promoter-terminators for single guide RNA (sgRNA) and BE component expression. We describe steps for designing and cloning sgRNA, synthetic target, and BE biomodules. We then detail procedures for BE module assemblage, E. coli transformation, and testing base editors and components.For complete details on the use and execution of this protocol, please refer to Shelake and Kim,1 Shelake et al.,2 and Shelake et al.3 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.